Amitriptyline for migraine prophylaxis in adolescents - Yazid Dimyati; Astri Nurhayati Zulkifli; Pranoto Trilaksono; Johannes H. Saing; Bistok Saing (Paediatrica Indonesiana, 2011)
headaches in children and adolescents. Amitriptyline efficacy as a prophylactic treatment for migraine in adults has been widely studied, but there is limited data on its use in children and adolescents.Objective To determine the efficacy of amitriptyline for prophylactic treatment of migraine in adolescents.Methods We conducted a single-blind, randomized, clinical trial study in Medan, North Sumatra, from July to October 2009. All participants had migraines, according to the International Headache Society criteria. They were divided into two groups, receiving either 10 mg amitriptyline or a placebo daily for 3 months. Headache frequency (days per month), headache duration (hours) and information to assess functional disability according to the Pediatric Migraine Disability Assessment Scale (PedMIDAS) were recorded by subjects. Efficacy was measured before, during and after intervention.Results A total of 98 patients, aged 12 – 19 years (mean age 14.7 years) enrolled and were divided into the amitriptyline and placebo groups. Compared with baseline, there were significant differences in headache frequency and PedMIDAS score in the amitriptyline group (P=0.001, 95% CI 2.02 to 2.94 and P=0.001, 95% CI 7.64 to 9.76, respectively), but not in the placebo group (P >0.05) after 3 months of treatment. We also found that amitriptyline significantly decreased headache frequency, duration, and functional disability compared to the placebo, after 3 months of treatment (P < 0.05).Conclusion Amitriptyline was effective for prophylactic treatment of migraine in adolescents after 3 months of intervention.